2017
DOI: 10.3389/fmed.2017.00193
|View full text |Cite
|
Sign up to set email alerts
|

Histological Grading of Hepatocellular Carcinoma—A Systematic Review of Literature

Abstract: BackgroundHistological grading typically reflects the biological behavior of solid tumors, thus providing valuable prognostic information. This is also expected in hepatocellular carcinoma (HCC), although limited access to biopsy samples and a lack of standardization might hinder its full predictive value in this cancer.ObjectivesIn order to better understand the current practices of histological grading in HCC, we examined the latest publications addressing its impact on the outcome of patients following surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 23 publications
4
81
3
Order By: Relevance
“…The degree of cell differentiation is usually associated with prognosis in HCC, despite the lack of consensus on HCC histological grading in the literature. 37 In this study, we found that high histological grades in the primary tumour were associated with the presence of distant metastases. Also, distant metastases were mainly constituted by poorly differentiated tumours, further suggesting the role of histological grading as a morphological proxy for HCC aggressiveness.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The degree of cell differentiation is usually associated with prognosis in HCC, despite the lack of consensus on HCC histological grading in the literature. 37 In this study, we found that high histological grades in the primary tumour were associated with the presence of distant metastases. Also, distant metastases were mainly constituted by poorly differentiated tumours, further suggesting the role of histological grading as a morphological proxy for HCC aggressiveness.…”
Section: Discussionmentioning
confidence: 58%
“…The degree of cell differentiation is usually associated with prognosis in HCC, despite the lack of consensus on HCC histological grading in the literature . In this study, we found that high histological grades in the primary tumour were associated with the presence of distant metastases.…”
Section: Discussionmentioning
confidence: 59%
“…Patient prognosis depends strongly on this phenotypic expression, which could be evaluated, for example, by analyzing pathological characteristics, such as the histological grade of the tumor [5] and microscopic vascular invasion [6]. Many staging systems including clinical, biological and imaging data have been developed such as the Barcelona Clinic Liver Cancer staging system [7], the Cancer of the Liver Italian Program [8,9], and the Okuda criteria [10].…”
Section: Introductionmentioning
confidence: 99%
“…The fixed tissues were then dehydrated in graded alcohol solutions, cleared in xylene and embedded in paraffin wax. Finally, 5 µm thick sections were cut, stained with H&E stain as was previously shown in . The slides were examined by an experimentally blinded histopathologist under a light microscope at 400× magnification power.…”
Section: Methodsmentioning
confidence: 99%